FACTORES QUE DETERMINAN LA CALIDAD DEL CORCHO - González Adrados, José Ramón (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
Cork quality, strongly related with economical profit 9f Quercus suber stands, is today determined by the visual characteristics of corkwood planks, mainly porosity and thickness. Variance in those'parameters is imputed to ecologic?l, selvicultural and genetic factors. Relationship between environmental factors and cork qua lit y is studied in this work. Data from two samples obteined in Extremadura and Catalonia show that this dependence is significati ve.
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: Cork; Cork quality; Quercus suber stands